New Zealand : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
This 2006 Article IV Consultation highlights that following a vigorous expansion in recent years, a cyclical slowing in New Zealand's economy commenced in 2005, with growth declining to 2u percent. Economic growth had averaged 4u percent annually in 2002-04, with domestic demand boosted by large migration inflows, wealth effects from rising housing prices, and income effects from high commodity prices. With slower growth easing resource pressures, inflation is expected to moderate, allowing an eventual easing in monetary policy.